Dwelling in-between. Issue 2 (1st December 2019) - Giddens, Sara; Judge, Tony; Law, John
AbstractChoreographer Sara Giddens reflects upon how making a series of ambulant performance works, The Dream-Walks, invited her to dwell in space‐times in-between, and how a resulting stepping aside heralded the opening up of a fundamental change in her relationship to audiences. Drawing upon a range of philosophers, including Bachelard, Heidegger and Rancière, Giddens reflects upon the impact that dwelling in those in-between space-times has had on her professional and pedagogic practice.16 short video clips, taken from the Eight Dream-Walks can be viewed at (https://www.bodiesinflight.co.uk/events/dwelling-in-between-choreographic-practices-102/ ).